KAJIAN HUKUM TENTANG PERLINDUNGAN KORBAN BULLYING: Legal Study On Protection Of Bullying Victims - Gede Tusan Ardika; Ramli Ramli; Aline Febriany Loilewen; Titin Titawati (PESOLAH: Jurnal Pendidikan, Sosial dan Humaniora, 2025)
Bullying cases are increasingly rampant, resulting in death or murder. The purpose of this study is to examine the law on the protection of bullying victims. The research method used in this writing is the normative legal research method and literature. The results of the study show that Indonesia is one of the countries that regulates protection for bullying victims and sanctions for perpetrators of bullying. Law Number 23 of 2002 concerning Child Protection (Child Protection Law), "Violence is any act against children that results in physical, psychological, sexual misery or suffering, and/or neglect, including threats to commit acts, coercion, or unlawful deprivation of liberty." Efforts to protect children have been regulated in several laws and regulations, including the Child Protection Law, Law No. 39 of 1999 concerning Human Rights and Law Number 11 of 2012 concerning the Juvenile Justice System (SPPA Law). Child protection is stipulated in Article 80 of Law Number 35 of 2014 concerning Amendments to Law Number 23 of 2002 concerning Child Protection